2021
DOI: 10.1111/ajae.12259
|View full text |Cite
|
Sign up to set email alerts
|

Rural broadband speeds and business startup rates

Abstract: Using 2014 U.S. nonmetropolitan county-level data, we explore the relationship between broadband speeds and business startup rates. Rural development policy discussions have presumed that access to broadband has become a necessary, although not sufficient, condition for economic growth and development.The relationship between broadband access on business startups, which are vital to local economic vibrancy, may be key to understanding the link between broadband and growth. In this study, we explore how qualita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 87 publications
(140 reference statements)
0
30
0
Order By: Relevance
“…Yet top internet access is particularly beneficial to heavy users dealing with large amounts of data, and some sectors are more likely to benefit. Among studies diving into the sectoral heterogeneity, Tranos and Mack (2016) studied KIBS in the US context and found strong correlations with broadband; a morerecent study of Deller et al (2021) confirms those results particularly for rural entrepreneurship in the US. Several studies used surveys to ask which industries use digital technologies (Forman et al, 2003), concluding in particular that "businesses in the information sector (NAICS 51) and management of companies and enterprises (NAICS 55) had the highest adoption rates of advanced Internet uses followed by finance and insurance businesses (NAICS 52) and businesses offering professional, scientific, and technical services (NAICS 54)" (Mack & Rey, 2014).…”
Section: Benefits Of Good Internet Connections: Nations Households An...mentioning
confidence: 74%
“…Yet top internet access is particularly beneficial to heavy users dealing with large amounts of data, and some sectors are more likely to benefit. Among studies diving into the sectoral heterogeneity, Tranos and Mack (2016) studied KIBS in the US context and found strong correlations with broadband; a morerecent study of Deller et al (2021) confirms those results particularly for rural entrepreneurship in the US. Several studies used surveys to ask which industries use digital technologies (Forman et al, 2003), concluding in particular that "businesses in the information sector (NAICS 51) and management of companies and enterprises (NAICS 55) had the highest adoption rates of advanced Internet uses followed by finance and insurance businesses (NAICS 52) and businesses offering professional, scientific, and technical services (NAICS 54)" (Mack & Rey, 2014).…”
Section: Benefits Of Good Internet Connections: Nations Households An...mentioning
confidence: 74%
“…The huge effort to get rural Americans high‐speed Internet connections, as documented by Isley and Low ( 2022 ), also may drive this result. The link between broadband and rural entrepreneurship is well documented, for example, Deller et al ( 2021 ), but in rural America the linkage between broadband adoption and moving existing businesses online is less clear, although evidence from O'Hara and Low ( 2020 ) suggests farm businesses in remote rural areas are benefiting from moving online.…”
Section: Policy Implications and Conclusionmentioning
confidence: 99%
“… Barba-Sánchez et al (2021) concluded that the information technology capabilities of entrepreneurs have a positive relationship with entrepreneurship. Deller et al (2022) studied the impact of broadband speed on local new venture creation, this article specifically divided broadband speed into several dimensions and found the indicators that most affect entrepreneurial outcomes, this line of research provides insights for our study. Tan and Li (2022) proposed that Internet technology has a greater effect on promoting entrepreneurship in rural areas of China than in cities, and the mechanism of action is to improve rural entrepreneurs’ access to information and financing.…”
Section: Introductionmentioning
confidence: 97%